Market Power in the German Wholesale Electricity Market - Felix Müsgens (Institute of Energy Economics at the University of Cologne (EWI), 2004)
This paper quantifies the degree of market power in the German wholesale electricity market. A fundamental model is used to derive competitive marginal cost estimators which are compared with observed electricity prices. Marginal costs are calculated focusing on market fundamentals such as plant capacities, fuel prices, and load structures. In addition, international power exchange and dynamic effects like start-up costs and hydro storage plant dispatch are incorporated. The comparison of marginal costs and prices reveals significant market power in the German electricity market, mainly exhibited during peak periods. Producer surplus is significantly increased by market power.
Keywords: C61; D43; L13; L94; 330; Market Power; Electricity Markets; Energy Modelling; Elektrizitätswirtschaft; Grosshandel; Marktmacht; Schätzung; Deutschland